All‐optical VPN platform for multisite VLC‐based networks. Issue 2 (22nd October 2018) - Salhi, Meriem; Sliti, Maha; Boudriga, Noureddine
Abstract: Optical networks and, in particular, visible light communication represent a very promising communication medium for future‐generation company networks. The establishment of virtual private networks (VPNs) in these specific distributed networks is a fundamental issue. In this paper, we present an all‐optical VPN platform based on visible light communication small cells on the access side and an optical fiber link on the backbone side. We exploited the security enhancement using the superposition of optical signals encoded using optical code‐division multiplexing codewords specific to each user. Two VPN modes are proposed: transport and tunnel. Even though the transport mode provides a much lower blocking rate as well as transmission performance (lower packet delay), the tunnel mode is advantageous from a security perspective due to the embedded optical code‐division multiple access encoding that it implements. Simulations are carried out for both modes to study the performance and security level provided by the proposed VPN architecture relatively to specific parameters (codeword size and number of simultaneous users). Abstract : In this paper, authors developed an all‐optical VPN enabling the establishment of secure optical communications between users within distributed sites. The transmission of the traffic through the optical path starts from the source VLC‐based OAP to reach the destination OAP, this traffic is aggregated and secured all‐optically thus avoiding conversion towards electronic domain. The proposed optical tunnelling scheme enhances confidentiality by exploiting double optical encryption.